2018
DOI: 10.1111/jcmm.13920
|View full text |Cite
|
Sign up to set email alerts
|

CPT1A‐mediated succinylation of S100A10 increases human gastric cancer invasion

Abstract: Gastric cancer (GC) is a malignancy of the lining of the stomach and is prone to distant metastasis, which involves a variety of complex molecules. The S100 proteins are a family of calcium‐binding cytosolic proteins that possess a wide range of intracellular and extracellular functions and play pivotal roles in the invasion and migration of tumour cells. Among these, S100A10 is known to be overexpressed in GC. Lysine succinylation, a recently identified form of protein post‐translational modification, is an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 46 publications
1
94
1
Order By: Relevance
“…For instance, S100A10 and annexin A2 can be used as candidate prognostic biomarkers of epithelial ovarian cancer 30 ; CPT1A-mediated S100A10 succinylation promotes the progression of GC. 25 Herein, we found that S100A10 expression was increased in HCC. Furthermore, our luciferase activity experiment proved that miR-320 could target S100A10.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…For instance, S100A10 and annexin A2 can be used as candidate prognostic biomarkers of epithelial ovarian cancer 30 ; CPT1A-mediated S100A10 succinylation promotes the progression of GC. 25 Herein, we found that S100A10 expression was increased in HCC. Furthermore, our luciferase activity experiment proved that miR-320 could target S100A10.…”
Section: Discussionmentioning
confidence: 73%
“…GAPDH, glyceraldehyde 3-phosphate dehydrogenase; miR-320, microRNA-320; NC, nitrocellulose therapy targets for HCC. 23 Serum miRNA-27a and miRNA-18b can serve as potential predictive biomarkers for hepatitis C-related HCC 24 ; the methylation of miR-183 is closely linked to a poor survival of HCC patients 25 ; miRNA-211 inhibits cell proliferation, migration and invasion by targeting SPARC in human HCC. 26 Similarly, this study found that miR-320 expression in HCC tissues was decreased than normal liver epithelial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Desuccinylation by SIRT5 suppresses the activities of pyruvate dehydrogenase complex and succinate dehydrogenase (117) leading to the accumulation of succinate and mitochondrial reactive oxygen species, thereby activating HIF1α (122). SIRT5 can also cause desuccinylation and negative regulation of S100A10, a protein that regulate invasion and motility (123). Generally, NAD + levels influence the secretion of various cytokines by inflammatory cells (124).…”
Section: Sirtuins In Tumor Angiogenesis and Their Regulatory Strategiesmentioning
confidence: 99%
“…Succinylated S100A10 was stabilized at the protein level by the suppression of its ubiquitylation. Moreover, carnitine palmitoyltransferase 1A (CPT1A) was found to function as a lysine succinyltransferase that regulates S100A10 succinylation . SIRT5 is a well‐known enzyme that catalyzes lysine desuccinylation in mammalian cells, as supported by the findings that SIRT5‐KO mice exhibit potently increased global lysine succinylation levels .…”
Section: The Role Of Acylation In Cancer Progressionmentioning
confidence: 99%